Cross-sectional study on accidental occupational exposures amongst urban slum-based private medical practitioners - Malgaonkar, Aniruddha A.; Kartikeyan, S.; Yadav, Yogesh K. (International Journal of Research in Medical Sciences, 2017)
Background:This cross-sectional, complete enumeration study was conducted in an urban slum to determine the frequency of occupational exposure of private medical practitioners to patient body fluids and the remedial measures adopted following such events and also to examine their high-risk practices, personal protective measures, immunisation and training status in relation to occupational exposures. Methods: After Institutional Ethics Committee approval, private medical practitioners practising for ≥ 1 year in the locality who gave written informed consent were interviewed in their own clinics using a pre-tested formatted questionnaire. Results: Of the 108 respondents interviewed, the majority were non-allopathic, male practitioners. The speciality-wise and gender-wise differences in training in occupational exposure were not significant (p=0.135). Prior to disposal, 10.18% cut needles while 26.85% disinfected needles with 1% hypochlorite solution (p=0.0001). 50.93% never bent or recapped needles (p=0.0008). Only 19.44% regularly used gloves while examining patients (p=0.0039). 41.66% were completely unimmunised against Hepatitis B (p=0.004), while only one female non-allopathic practitioner (0.92%) had taken complete immunisation against tetanus (p<0.05). Of the 7.41% respondents who had history of needle stick injuries, only one female non-allopathic practitioner had reported occupational exposure. Those unaware about the need for post-exposure prophylaxis for occupational exposure and that anti-retroviral therapy was part of post-exposure prophylaxis constituted 87.96% and 95.37%, respectively. Conclusions: Reporting of occupational exposure, complete immunisation against hepatitis B and tetanus and use of personal protection was inadequate. Specialised hands-on training ought to be an integral component of continuing medical education for private medical practitioners.